Implementação do sistema de cristalização superficial induzida por laser em vidro de composição eutética - Nunes, Ângela Santana (Universidade Federal de São Carlos, 2019)
The radiation from lasers has been successfully applied to materials processing such as drilling, cutting and welding, sintering of ceramic oxides, surface heat treatment, directional solidification of single crystal fibers and texturing of crystalline compounds. The characteristics that make the laser radiation attractive to surface heat treatment processing are its coherence and collimation, which allowed the spatial control of the thermal energy. The modification of the material´s surface is dependent on the composition of the sample, the power of the laser and the radiation exposure time. Thus, the efficiency of crystallization, scalability and the possibility of local heating are some of the main attributes of laser crystallization. In addition, the laser can be used to induce crystallization on an amorphous substrate. Low cost of production is the main feature offered by laser crystallization to become an ideal solution for many industrial applications. A laser writing system can lead to the development of devices that can operate in aggressive environment like an acid or at high temperatures. Thus, the present work has the objective of developing versatile, low cost and programmable laser writing system, which allows the superficial heat treatment in glasses. In this work a CO2 laser source was used, which allowed the production of superficial crystallization. For the study of the developed system, it was chosen an eutectic composition glass (system LiO2.SiO2-CaO.SiO2), as the material model, in order to verify the control of the microstructure. After the crystallization the identified crystalline phases were calcium and lithium metassilicate, independent of the laser scanning speed. The microstructure formed and the depth of the heat affected zone shows a dependency with the laser scanning speed. Finally, it was found that the average interphase spacing obeys a similar relationship described by Jackson and Hunt for the solidification of eutectic systems, that is, by controlling the laser scanning speed it is possible to control the formed microstructure and thereby obtain the control of the final properties of the material.
Implementation of a surface crystallization system induced by laser in eutectic composition glass
Keywords: Técnica de cristalização; Sistema eutético; Crystallization technique; Eutectic system; Lasers; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA